Public Health, Human Capital, and Economic Growth: The Lasting Effects of Disease Control in China - He, Fan; Huang, Wei; Pan, Yinghao; Wang, Jiao (The Review of Economics and Statistics, 2026)
Abstract This paper investigates the long-term impacts of China’s nationwide public health campaigns targeting malaria, measles, and meningitis between the 1960s and 1980s. Exploiting regional variation in precampaign disease prevalence across birth cohorts, we show that these interventions generated sizable improvements in education, cognition, health, and income. As an illustrative case, individuals from high-malaria regions who were fully exposed to the eradication campaign attained about 0.5 additional years of schooling and earned over 10% higher income in adulthood, with cognitive and schooling gains explaining a substantial share of the income effects. Extending the same approach to measles and meningitis vaccination campaigns reveals comparably large benefits, with internal rates of return ranging from 21% to 34%. Together, these findings highlight the lasting socioeconomic returns to early-life health interventions and underscore the role of public health as a foundation for human capital accumulation and long-run economic growth.